Determinants of Customer Loyalty in Casual Dining Restaurants (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
In today’s highly competitive food service industry, casual dining restaurants face the constant challenge of not only attracting customers but also retaining them. Customer loyalty has become a crucial success factor, especially as consumer expectations evolve and choices expand. Unlike fast food or fine dining establishments, casual dining restaurants must strike a balance between quality, affordability, and service consistency. Understanding what drives customer loyalty in this segment is essential for restaurant operators aiming to sustain long-term business growth. This study seeks to explore the primary determinants influencing customer loyalty in casual dining settings by examining factors such as service quality, food quality, ambiance, price fairness, and perceived value.This study explores the key determinants of customer loyalty in casual dining restaurants, focusing on factors such as service quality, food quality, ambiance, price fairness, customer satisfaction, and perceived value. Using a quantitative approach, survey data were collected from patrons of selected casual dining establishments and analyzed to determine the relationship between these factors and customer loyalty. Results show that service and food quality are strong predictors of loyalty, with customer satisfaction and perceived value acting as mediators. The findings offer practical insights for restaurant managers to enhance service delivery and foster customer retention.